Investigating the Effect of Earmuffs and Eyeshields on Pain Caused by Orogastric Tube Insertion among Infants in Neonatal Intensive Care Unit - Akram sadat Sadat Hoseini; Ashraf Ajam Hassani (Journal of Mazandaran University of Medical Sciences, 2020)
Background and purpose: Reducing sensory and environmental stimuli such as visual and auditory stimuli is one of the non-pharmacological methods to relieve pain. The purpose of this study was to examine the effect of eye shields and earmuffs on pain caused by orogastric tube insertion in infants. Materials and methods: A clinical trial was carried out in teaching hospitals affiliated with Tehran University of Medical Sciences in 2018. Seventy six infants were selected by convenience sampling and were randomly placed in an intervention group or a control group. Earmuffs were used since four hours before orogastric tube insertion and eye shields were used two hours before the procedure. A camera recorded facial expressions and the heart rate and oxygen saturation were also recorded for 15 seconds in resting position, before the procedure, during, and 30 seconds after orogastric tube insertion. Pain intensity during the procedure was assessed in both groups using Premature Infant Pain Profile (PIPP). Data were analyzed using t-test, Mann Whitney, Wilcoxon, Friedman test, and Chi-square test. Results: The study showed significant differences in mean score for pain during and after orogastric tube insertion between intervention group (4.29 ± 2.67and 1.16 ± 0.26) and control group (9.11 ± 1.80 and 4.24 ± 2.55), respectively (P=0.001). Conclusion: According to this study, eye shields and earmuffs could be used before orogastric tube insertion in order to relieve pain.